2007
DOI: 10.1152/ajpgi.00338.2004
|View full text |Cite
|
Sign up to set email alerts
|

Supramaximal CCK-58 does not induce pancreatitis in the rat: role of pancreatic water secretion

Abstract: In contrast to supramaximal CCK-8 or caerulein, acute or prolonged supraphysiological levels of endogenous CCK-58 do not cause pancreatitis. Compared with CCK-8, CCK-58 is a much stronger stimulant of pancreatic chloride and water secretion, equivalent to maximally effective secretin, but with a chloride-to-bicarbonate ratio characteristic of acinar fluid. Because supraphysiological endogenous CCK does not cause pancreatitis and because coadministration of secretin ameliorated caerulein- or CCK-8-induced pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…It has been reported that, in contrast to supramaximal CCK-8 or caerulein administration, supramaximal levels of CCK-58 do not cause pancreatitis. This is possibly attributable to the previously reported observation that supramaximal CCK-58 maintains pancreatic acinar water secretion, which is essential for exocytosis of activated zymogens (25). Clearly, therefore, a disruption to the water flow is one of the contributing factors in the onset of pancreatitis.…”
Section: Discussionmentioning
confidence: 89%
“…It has been reported that, in contrast to supramaximal CCK-8 or caerulein administration, supramaximal levels of CCK-58 do not cause pancreatitis. This is possibly attributable to the previously reported observation that supramaximal CCK-58 maintains pancreatic acinar water secretion, which is essential for exocytosis of activated zymogens (25). Clearly, therefore, a disruption to the water flow is one of the contributing factors in the onset of pancreatitis.…”
Section: Discussionmentioning
confidence: 89%
“…CCK-58 induces a more sustained pancreatic protein secretion than CCK-8, as shown by the return to basal values at the end of the 3-h infusion period with CCK-8, whereas protein output remained significantly elevated compared with basal in CCK-58-treated rats (46,62). In addition, intravenous infusion of CCK-58 at 2 or 4 nmol·kg Ϫ1 ·h Ϫ1 for 6 h in a conscious rat model did not induce pancreatitis at a dose at which CCK-8 induced several parameters indicative of pancreatitis, including interstitial edema, inflammatory cell infiltration, intracellular vacuolization, increased pancreatic myeloperoxidase activity, and elevated serum amylase levels (61).…”
Section: ·Hmentioning
confidence: 83%
“…CCK-8 AND CCK-58: EFFECT ON FEEDING PATTERN (61). Sayegh and coworkers (33) have shown that effects of endogenous CCK on meal size and IMI are partly regulated by the CCK 1 receptor (55).…”
Section: R855mentioning
confidence: 99%
“…There were regenerative changes on day 7 and day 14, with almost a complete recovery of zymogen granules by day 14. In contrast to supramaximal CCK-8 or caerulein, acute or prolonged supraphysiological levels of endogenous CCK-58, the only detectable endocrine form in the rat (Reeve et al, 2003), do not cause pancreatitis (Yamamoto et al, 2007). The response of rat pancreatic cells is limited and a down-regulation of the receptor CCK-A has been suggested as a protective mechanism (Ohlsson et al, 2000).…”
Section: Discussionmentioning
confidence: 99%